The human carbonic anhydrase isoenzymes I and II (hCA I and II) inhibition effects of trimethoxyindane derivatives - Taslimi, Parham; Gülçin, İlhami; Ozgeris, Bunyamin; Goksu, Suleyman; Tumer, Ferhan; Alwasel, Saleh H.; Supuran, Claudiu T.; Taslimi, Parham (Informa, 2016)
Carbonic anhydrases (CAs, EC 4.2.1.1) had six genetically distinct families described to date in various organisms. There are 16 known CA isoforms in humans. Human CA isoenzymes I and II (hCA I and hCA II) are ubiquitous cytosolic isoforms. Acetylcholine esterase (AChE. EC 3.1.1.7) is a hydrolase that hydrolyzes the neurotransmitter acetylcholine relaying the signal from the nerve. In this study, some trimethoxyindane derivatives were investigated as inhibitors against the cytosolic hCA I and II isoenzymes, and AChE enzyme. Both hCA isozymes were inhibited by trimethoxyindane derivatives in the low nanomolar range. These compounds were good hCA I inhibitors (Kis in the range of 1.66-4.14nM) and hCA II inhibitors (Kis of 1.37-3.12nM) and perfect AChE inhibitors (Kis in the range of 1.87-7.53nM) compared to acetazolamide as CA inhibitor (Ki: 6.76nM for hCA I and Ki: 5.85nM for hCA II) and Tacrine as AChE inhibitor (Ki: 7.64nM).
Keywords: Acetylcholine esterase; Enzyme inhibition; Enzyme purification; Trimethoxyindane derivatives; Affinity chromatography; Carbonic anhydrase